THE ANALYSIS OF EMPLOYESS’ FEEDBACK ON THE CHANGE MANAGEMENT IMPLEMENTATION AT PT. AIR MANADO - Sasauw, Ivan David; Massie, James D.D; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Every company or organization must change to survive. In evaluate the change that implanted, feedback is one of a tool that usually used. This research is aims to analyse the employees’ feedback of the change management that implemented at PT. Air Manado specifically in Production and Laboratory that changed their manager. This research is a qualitative research with using in-depth interview in collecting and analysing the data and this research is exploratory study research to find out what phenomena that are happening. Snowball sampling is used. Result discovers some issues that appear in disciplinary, job rotation, leadership, and employees’ trust. Other way, employees also complains about their job safety and financial welfare that must be concerned. What needed from a manager is capable to socialize with subordinates. There must be a courage to fight for employees or subordinates in higher level of meetings and in taking action for subordinates’ lamentation. In job placement at PT. Air Manado and other companies, it is better to not to get intervened by outsiders, high-up people, political parties, and regional government to better the morale and professionallism. Company needs to pay more attention to employee’s welfare.Keywords: human resource management, change management, employee’s feedback